19 Reducing the match day injury rate at a semi-professional rugby club: an audit of injury between 2013 and 2015. (13th October 2015) - Smith, R; Downing, W; Thompson, D; Fitch, S; Bowler, S
Abstract : Rugby Union (RU) has a high incidence of injuries. The predominant focus of the epidemiological data has been on elite RU players. There is limited specific incidence data for semi-professional players. Effective injury prevention strategies have focused on primary prevention including warm up, safe playing techniques and rule changes. This prospective audit aimed to: i) establish the incidence (per 1000 player match hours) and severity of injuries (time lost) at a semi-professional rugby union club (SPRUC) ii) assess the introduction of an injury prevention strategy. Over the season of 2013/14, injury information regarding event, type, playing position and severity (days missed through injury) for all senior male first team players was recorded using the Benchmark 54 injury analytics software. Any injury resulting in 8 days or greater absence from match play was recorded as a time loss injury (TLI). Following initial findings, recommendations including the addition of a strength and conditioning coach to the multi-disciplinary team, changes to the players warm up and specific conditioning exercises were implemented. In the following season of 2014/15 the audit was repeated. The number of TLIs fell from 35 (1.06/match) in 2013/14 to 23 (0.69/match) in 2014/15. The overall match injury incidence reduced from 54.1 to 35.7/1000 playing hours. However, the median time to return to play from injury remained comparable, 30 days (2013/14) and 34 days (2014/15). In both seasons the most common injury sites were ankle, knee and shoulder. Contact events accounted for 67% (39/58) of all injuries, of these 64% (25/39) were sustained in the tackle. These findings show that there was a reduction in injury rate between seasons but not severity. We postulate that this may have been influenced by our interventions. Future studies should focus on a larger cohort of SPRUC auditing injuries undergoing specific preventative strategies in order to reach firmer conclusions.